2020
DOI: 10.1002/anie.202001737
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Cobalt Phosphates with Modulated Coordination Sites for Electrocatalytic Water Oxidation

Abstract: The correlation between metal coordination and electrocatalytic water oxidation performance is elusive in many cobalt-based materials. Herein, we designed an ideal Co phosphate-based platform to explore the effect of coordination environment on oxygen evolution reaction (OER) activity. The cobalt geometry was modulated from octahedral to tetrahedral by simple removal of water ligands in Co 3 (PO 4 ) 2 ·8 H 2 O. Other features except the coordination structure in the two autologous materials remain similar. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(83 citation statements)
references
References 41 publications
8
75
0
Order By: Relevance
“…realized the transformation of cobalt phosphate from octahedron to tetrahedron by dehydration at high‐temperature treatment. [ 119 ] The electrocatalytic results showed that Co 3 (PO 4 ) 2 with cobalt tetrahedron had higher activity than that of Co 3 (PO 4 ) 2 ·8H 2 O with cobalt octahedron, which was attributed to that Co tetrahedral site could promote the formation of high‐valent cobalt active species in OER. Besides, the phosphate group has also been confirmed to be proton acceptors and can induce distorted local structure, and thus is conducive to water adsorption and catalytic oxidation.…”
Section: Complete Reconstruction For Oermentioning
confidence: 99%
“…realized the transformation of cobalt phosphate from octahedron to tetrahedron by dehydration at high‐temperature treatment. [ 119 ] The electrocatalytic results showed that Co 3 (PO 4 ) 2 with cobalt tetrahedron had higher activity than that of Co 3 (PO 4 ) 2 ·8H 2 O with cobalt octahedron, which was attributed to that Co tetrahedral site could promote the formation of high‐valent cobalt active species in OER. Besides, the phosphate group has also been confirmed to be proton acceptors and can induce distorted local structure, and thus is conducive to water adsorption and catalytic oxidation.…”
Section: Complete Reconstruction For Oermentioning
confidence: 99%
“…Density functional theory calculations revealed that Na 2 CoP 2 O 7 had low energy barrier and the OER pathway in Na 2 CoP 2 O 7 used 4‐ and 5‐coordinated cobalt atoms stabilized by actively rotating pyrophosphate groups. Moreover, further studies indicate the higher intrinsic activity from Co tetrahedral sites is their facilitation on forming active high valent cobalt (hydro)oxide intermediates during OER [39] . Additionally, it has been reported NaCo 4 (PO 4 ) 3 with 5‐coordinations have better OER catalytic performance in neutral solution compared with Na 2 CoP 2 O 7 with 4‐coordinated Co configurations [40] …”
Section: Design Strategies For Highly Efficient Transition‐metal Phosmentioning
confidence: 98%
“…Inorganic porous materials display interesting physical properties, such as magnetic, heterogeneous catalysis, adsorption/separation, and ion‐exchange due to their diverse composition of metal ions and unique porous structure [1–9] . Among them, porous transition‐metal phosphates have been attracting wide attention in renewable energy conversion and storage technology, [2,3] such as supercapacitors, [10,11] metal‐air batteries, especially, hydrogen energy from water splitting [2,12–16] . However, the overpotential at 10 mA/cm 2 for oxygen evolution reaction (OER) in the process of water splitting, corresponding to 10 % solar‐to‐fuel conversion efficiency, is still significantly higher than the standard potential of ∼1.23 V because it involves multiple proton‐coupled electron transfers (PCET) process, leading to its sluggish kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Among them, porous transition-metal phosphates have been attracting wide attention in renewable energy conversion and storage technology, [2,3] such as supercapacitors, [10,11] metal-air batteries, especially, hydrogen energy from water splitting. [2,[12][13][14][15][16] However, the overpotential at 10 mA/cm 2 for oxygen evolution reaction (OER) in the process of water splitting, corresponding to 10 % solar-to-fuel conversion efficiency, is still significantly higher than the standard potential of~1.23 V because it involves multiple proton-coupled electron transfers (PCET) process, leading to its sluggish kinetics. Many electrocatalysts such as metal-based oxysalts: oxides/hydroxides, [8] phosphates and borates, [2,3] especially, porous transition-metal phosphates with H 2 PO 4 À or HPO 4 2À unique proton acceptors, have shown superb electrocatalytic performance toward OER in local pH environment, thus, they have been widely used as promising candidates owing to their various metal coordination configuration and structural stability.…”
Section: Introductionmentioning
confidence: 99%